Muslim Progresif: Jembatan antara Tradisi dan Modernitas dalam Pandangan Islamic Worldview - Firdiana, Linda; Muarifah, Muarifah; Sani, Mutiara; Sumiran, Sumiran (TSAQOFAH, 2025)
The term "progressive Muslim" has become increasingly prominent in contemporary Islamic thought, referring to individuals or groups who interpret Islamic teachings contextually, respond actively to the dynamics of the times, and emphasize values such as social justice, gender equality, human rights, and pluralism. This article aims to explore the definition of progressive Muslims and analyze their position and role within the framework of the Islamic worldview. A qualitative approach was employed using literature study methods, focusing on the works of prominent progressive Muslim thinkers and supported by critical analysis of relevant literature. The findings reveal that progressive Muslims engage not only in the reinterpretation of religious texts but also in reaffirming Islam's relevance to modern challenges while maintaining a connection to its traditional roots. Within the perspective of the Islamic worldview, progressive Muslims are seen as agents of change who integrate the principles of maqashid syariah to bridge the gap between tradition and modernity. As such, the progressive approach is crucial for preserving Islam’s continuity and adaptive capacity in a complex and dynamic era of globalization.